2010
DOI: 10.1371/journal.pntd.0000902
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Simple Lymphoedema Treatment Regimen in Podoconiosis Management in Southern Ethiopia: One Year Follow-Up

Abstract: BackgroundPodoconiosis is a non-filarial elephantiasis caused by long-term barefoot exposure to volcanic soils in endemic areas. Irritant silicate particles penetrate the skin, causing a progressive, debilitating lymphoedema of the lower leg, often starting in the second decade of life. A simple patient-led treatment approach appropriate for resource poor settings has been developed, comprising (1) education on aetiology and prevention of podoconiosis, (2) foot hygiene (daily washing with soap, water and an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 15 publications
1
86
1
Order By: Relevance
“…37 Treatment of affected individuals comprises foot hygiene, bandaging where indicated, use of socks and shoes, exercises to improve lymph flow, and elevation of the legs while sleeping, and treatment seems effective in improving clinical outcomes and quality of life. 38 Accordingly, the MFTPA orally delivered health education curriculum emphasizes the importance of wearing shoes and properly cleaning feet each day. The curriculum has not included any emphasis on improving understanding of the causes of the condition.…”
Section: Methodsmentioning
confidence: 99%
“…37 Treatment of affected individuals comprises foot hygiene, bandaging where indicated, use of socks and shoes, exercises to improve lymph flow, and elevation of the legs while sleeping, and treatment seems effective in improving clinical outcomes and quality of life. 38 Accordingly, the MFTPA orally delivered health education curriculum emphasizes the importance of wearing shoes and properly cleaning feet each day. The curriculum has not included any emphasis on improving understanding of the causes of the condition.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, patients who had positive attitude towards podoconiosis management were six times more likely to show success in treatment outcome of lymphoedema management, AOR= 5.64 (3.18, 9.99). In one year follow-up study done by Sikorski et al (2014) to see the effectiveness of a simple lymphoedema treatment regimen in podoconiosis management in Wolaita Zone, Southern Ethiopia, it was observed that patients' self commitment was an important condition to see clinical outcomes of lymphoedema treatment in podoconiosis management [17].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was designed to include questions about socio-demographic characteristics, clinical history, and treatment seeking behavior, shoe wearing habits and personal hygiene practices, treatment duration and outcome, and perception Among Podoconiosis Patients in Wolaita Zone, Southern Ethiopia of the subjects after treatment. Lymphoedema management success was then determined based on self reported response and observation [17].…”
Section: Data Collection Proceduresmentioning
confidence: 99%
See 2 more Smart Citations